2015
DOI: 10.1016/j.actamat.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale properties of Ni-based FCC ternary, and quaternary alloys

Abstract: Keywords:High entropy alloy Density functional theory Monte Carlo Short-range order Ni based alloys a b s t r a c t The aim of this study is to characterize some atomic-scale properties of Ni-based FCC multicomponent alloys. For this purpose, we use Monte Carlo method combined with density functional theory calculations to study short-range order (SRO), atomic displacements, electronic density of states, and magnetic moments in equimolar ternary NiCrCo, and quaternary NiCrCoFe alloys. According to our study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
88
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(104 citation statements)
references
References 34 publications
15
88
0
1
Order By: Relevance
“…Short-range order is not rare in conventional alloys and it has obvious effect on the physical properties and materials performance [22][23][24]. Due to the chemical complexity, SRO is expected in HEAs and was predicted by density-functional theory recently [25,26]. However, no direct experimental evidence of SRO in HEAs has been reported.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Short-range order is not rare in conventional alloys and it has obvious effect on the physical properties and materials performance [22][23][24]. Due to the chemical complexity, SRO is expected in HEAs and was predicted by density-functional theory recently [25,26]. However, no direct experimental evidence of SRO in HEAs has been reported.…”
mentioning
confidence: 95%
“…Effects of SRO on the electrical resistivity of alloys have been studied theoretically and experimentally before [24,26,39]. For example, resistivity increases by 20-30% with the formation of SRO in NiCu alloys [42], which is not as markedly in NiCoCr compared with binary NiCo.…”
mentioning
confidence: 99%
“…Density-functional-theory (DFT) calculations for FeCoNiCr and FeCoNi revealed that electronic charge transfer causes a local atomic pressure on the individual constituents, which could result in local volume fluctuations [19]. Further DFT studies revealed strong element-specific magnetic moment fluctuations in fcc FeCoNiCr, which are ultimately rooted in local electronic structure effects [20][21][22]. In particular anti-ferromagnetic Cr plays a crucial role [20].…”
Section: Introductionmentioning
confidence: 99%
“…For some multicomponent alloys, the forming of intermetallic or even metallic glasses makes the role of mixing entropy questionable. In the past decade [5][6][7][8][9][10][11][12][13], some elements had been shown to help form the face centered cubic solid-solution phases, such as copper, and nickel, on the contrary, aluminum and chromium favour the forming of body centered cubic phases. Recently, a six-component high entropy alloy system of CoCrFeNiCu x Al 1-x has been explored and effects of lattice distortion on the phase transformation of the as-cast alloys have been studied [14].…”
Section: Introductionmentioning
confidence: 99%